Effects of Hydrostatic Pressure and Temperature on the Uptake and Respiration of Amino Acids by a Facultatively Psychrophilic Marine Bacterium - Paul, Kala L. (1971)
Studies of pressure and temperature effects on glutamic acid transport and utilization indicated that hydrostatic pressure and low temperature inhibit glutamate transport more than glutamate respiration. The effects of pressure on transport were reduced at temperatures near the optimum. Similar results were obtained for glycine, phenylalanine, and proline. Pressure effects on the transport systems of all four amino acids were reversible to some degree. Both proline and glutamic acid were able to protect their transport proteins against pressure damage. The data presented indicate that the uptake of amino acids by cells under pressure is inhibited, which is the cause of their inability to grow under pressure.